Improvement in Fatigue during Natalizumab Treatment is Linked to Improvement in Depression and Day-Time Sleepiness - Penner, Iris-Katharina; Sivertsdotter, Eva Catharina; Celius, Elisabeth G.; Fuchs, Siegrid; Schreiber, Karen; Berkö, Sara; Svenningsson, Anders; , for the TYNERGY trial investigators (Frontiers in Neurology, 2015)
Background: Fatigue is a frequent symptom in multiple sclerosis (MS) and often interrelated with depression and sleep disorders making symptomatic treatment decisions difficult. In the single-arm, observational phase IV TYNERGY study, relapsing–remitting MS patients showed a clinically meaningful decrease in fatigue over 1 year of treatment with natalizumab. Objective: To evaluate whether fatigue improvement might be directly linked to improved depression and day-time sleepiness. Methods: Patients were assessed regarding fatigue, depression, and day-time sleepiness. The relation between changes of the two latter symptoms and changes in fatigue was analyzed. Results: After 1 year of natalizumab treatment, the majority of patients (>92%) remained stable or improved in total, motor, and cognitive fatigue. Proportion of patients without depression increased by 17% while proportions of mildly depressed patients or patients with potential major depression decreased by 5 and 12%, respectively. Proportion of patients classified as not being sleepy increased by 13% while proportions of sleepy and very sleepy patients decreased by 11 and 2%, respectively. Most importantly, improved depression and sleepiness were significantly related to improved fatigue. Conclusion: Our findings highlight the importance of patient-reported outcomes in identifying potential benefits of drug treatment beyond its well-established effects on disease activity and disability progression.